Pengaruh Ekstrak Daun Dan Buah Ketapang Terhadap Malondialdehida Pankreas Rattus Norvegicus Jantan yang Diinduksi Aloksan dan Diet Tinggi Lemak - LYBELARY DEWI SATRIANAWATY; FRANSISKA CHRISTELA; ANTHONY ANUGERAH JOSHUA; SULISTIANA PRABOWO (HANG TUAH MEDICAL JOURNAL, 2019)
ABSTRACT Background : Diabetes mellitus is a chronic disease caused by high levels of blood glucose. Hyperglycemia will cause the formation of free radicals which can damage cells. To reduce this effect, antioxidants are needed. Aloksan is a chemical that can damage beta cells, resulting in decreased insulin production. Ketapang (Terminalia catappa) is a plant that can be used because of its antioxidant content. The administration of ketapang extract is thought to reduce levels of malondialdehyde. Malondialdehyde is a biomarker for the occurrence of lipid peroxidation in the body caused by an increase in free radicals due to the occurrence of oxidative stress. Metode : 32 male rats divided into 4 groups. Three groups will be given high-fat diet for 7 days followed by induced alloxan at a dose of 90 mg / kgBW to increase blood glucose levels and pancreatic malondialdehyde levels. Then 2 groups will be given treatment for 14 days. The first treatment group was given Ketapang extract with a dose of 600 mg / kgBW and the second treatment group which was given glibenclamide using a dose of 0.09 mg / kgBW. Results: administration of ketapang leaf and fruit extract reduced the levels of molondialdehyde in Wistar rats given a high fat diet and induced by alloxan, but did not significant (p = 0.916). There was a significant reduction in malondialdehyde in Wistar rats given glibenclamide (p = 0.016). Conclusions: the administration of ketapang leaf and fruit extract were able to reduce the levels of pancreatic malondialdehyde given a high-fat diet and induced by alloxan.